Akselerasi Pelatihan Manajemen Sumber Daya Industri ( Digital Marketing ) - Aprila, Bord Nandre; Purnama, Intan; Prihastomo, Arih Dwi; Novrizal, Dedy; Martias, Fery; Handoyo, Leonardus Teguh; Azmi, Fauzan; Farhas, Rizqon Jamil (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
The development of digital technology has driven changes in marketing patterns. This community service activity aims to accelerate the improvement of industrial human resource (HR) capacity through digital marketing-based industrial resource management training. The training focuses on strengthening the application of management functions in the context of digital marketing, emphasizing the optimization of industrial resources, including human, financial, material, machine, method, and market aspects. The implementation method is participatory training, integrating concept presentations, interactive discussions, and hands-on practice. The training materials covered the basics of digital management, the use of social media and digital platforms as marketing tools, the implementation of segmentation strategies, market targeting and positioning (STP), and the development of a marketing mix in the digital era. The results of the activity showed an increase in participants' abilities in designing and managing digital-based promotions, optimizing the use of e-commerce platforms, and building a more adaptive and competitive brand image. These findings indicate that accelerating industrial resource management training through digital marketing is an effective strategy for increasing the competitiveness and readiness of industrial human resources in facing the challenges of the Industry 4.0 era.